Cost-benefit analysis of kenaf as biomaterial for automotive components - Ong, Chu Lee (2015)
Kenaf is known as a renewable source of material that has various industrial applications. Recognized as a cash crop, it had been brought into Malaysia and was targeted to become one of the major commodities for the country. Among myriads of application, its use as bio-material for automotive components had proved viable in many technical studies. Moreover, by replacing kenaf with conventional fossil based feedstock; it can improve automobile efficiency by weight reduction which in turns brings fuel savings and avoid corresponding CO2 emission. Furthermore, kenaf is also known for its high carbon absorption ability relative to other plants which can aid in reducing global warming. In conjunction with national kenaf development programs, kenaf venturing into automotive industry seemed encouraging. However, to tap into the restrictive automotive industry; more insights and planning are needed. Thus, the advent of this study is targeted to reveal the feasibility of kenaf applications as biomaterial for automotive components with financial and economic viewpoints. Using cost-benefit analysis, this study has three consecutive objectives. The first is to identify the processes and procedures for kenaf as feedstock for automotive parts in Malaysia. Secondly, is to determine and estimate the relevant cost and benefits involve in the value chain identified. Third, is to assess the financial and economic feasibility of kenaf applications as bio-material for automotive components. This analysis enables the recognition and accounting of direct and indirect costs and benefits in monetary units to uncover the financial and economic feasibility of the project. As a result, the findings suggest that applying kenaf as bio-material for automotive components is generally viable financially and economically. However, looking at the four production stages identified – kenaf cultivation, fibre processing, compounded and non-woven composite sheets production, and utilisation into automobile parcel shelves; the results were mixed. The utilisation of kenaf as bio-material for automotive components can be financially and economically feasible with rising scale of production and with kenaf price reduction. The findings also suggest that more efforts are needed in improving competitiveness of kenaf and kenaf fibre production to enable its penetration to the automotive sector. In addition, policies are needed to promote utilisation of natural fibre in automotive industry.